DIGITAL CONTENT MODEL DEVELOPMENT OF LEARNING USING R&D METHOD TO ENHANCED DIGITAL LITERACY COMPETENCY (International Journal of Psychosocial Rehabilitation, 2020)
The development of information technology has changed the way humans get information and learn. It's just that many other aspects that are still considered lacking in handling content. Much digital content is transformed into digital format without regard to the correct aspects of digital content. Whereas digital literacy competence should enable people to be skilled in responding to the development of technology and the internet today in the Industrial 4.0 era. For this reason, a digital content model has been developed that is implemented in learning using R&D methods that accommodate important aspects of content, especially information technology. Based on the description of the problem identification above, it is identified that there are no standards in creating a good digital content model. Development of digital content models that become guidelines in creating digital content to improve digital literacy competencies of students and digital society, with six components including: Digital Attributes such as digital media, Search Engine Optimization (SEO), digital copyright and Social Studies Education, governance write, as well as knowledge. Digital content was launched on the User Generated Content Platform. The research results show that learning digital content models can improve digital literacy competencies based on pre-test and post-test, attitude scale assessment and significance test.